Microfluidics modelling of interstitial flow through a tumor and the study of tumor cell under dielectrophoresis - Tay, Benjamin Zikai (Nanyang Technological University, 2021)
90% of cancer-related mortalities are due to the metastatic spread of cancer. Interstitial pressure and flow within the tumor microenvironment have been identified to be influential in the metastatic spread of cancer. This study focuses on biophysical effect of interstitial pressure and flow on the detachment of MCF-7 cells of varying expression levels of E-cadherins from primary tumor. The expression levels of E-cadherins affects the intercellular adhesivity of MCF-7 cells which relates to the varying degree of invasiveness in cancers. This allows for the study of heterogeneity of MCF-7 cells which closely mimics the in vivo tumor. To affect the expression levels of E-cadherins, MCF-7 cells are cultured in 1.5mM, 1.7mM and 1.9mM calcium concentration culture medium. MCF-7 cells cultured in different calcium concentration medium are observed and measured for size and shape differences to study the morphological differences. There are significant morphological differences. ELISA test is conducted, and the results show that the expression level of E-cadherin in MCF-7 cells cultured in 1.5mM calcium concentration culture medium is 1.46 times lower than MCF-7 cells cultured in 1.7mM calcium concentration culture medium and 2.20 times lower than MCF-7 cells cultured in 1.9mM calcium concentration culture medium. Flow is introduced to MCF-7 aggregate in a microfluidic device and pressure differences between the afferent and efferent ends are recorded at 1s time interval. Fluid flows through the porous aggregate at a slower rate than the flow rate at the afferent end causing an increase in pressure difference. Under high loading rate (1μl/min2), for MCF-7 aggregates cultured in 1.9mM calcium concentration culture medium, which express higher E- cadherin, fracture in aggregates which mimics the detachment of the tumor cells from the primary tumor is observed at a pressure difference of 1036Pa. For MCF-7 aggregates cultured in 1.7mM and 1.5mM calcium concentration culture medium, fracture is observed at a pressure difference of 510.2Pa and 321Pa respectively. These findings show that MCF-7 cells with higher expression of E-cadherins can withstand higher pressure buildup at the afferent ends and fractures occur and detach at a higher critical fracture pressure than MCF-7 cells with lower expression of E-cadherins. Under low loading rate (0.5μl/min2), the mean critical fracture pressure is not affected by the change in E-cadherin expression levels. The role of extracellular matrix in the detachment of MCF-7 cells is also studied by varying the fibronectin concentration in the coating of microfluidic device. Results show that an increase in fibronectin concentration which translates to stronger cell-ECM adhesions would cause an increase in mean critical fracture pressure. A simple DEP setup was used on MCF-7 cells. DEP induced lateral movement of MCF-7, forming chain of MCF-7 cells that are parallel to the microelectrodes. Under positive DEP, MCF-7 cells are attracted to the microelectrodes. Under negative DEP, MCF-7 cells are repelled away from the microelectrode to form a chain of cells. The cells adhere to each other. This opens up opportunity for collection of this chain of MCF-7 cells to study single cell-cell adhesion on MCF-7.